EFFECT OF KRAFT PULPING TEMPERATURE AND ALKALINITY ON EUCALYPTUS ECF BLEACHING - Ventorim, Gustavo [UNESP]; Comelato Favaro, Jaqueline Silveira [UNESP]; Frigieri, Tania Cristina [UNESP] (Editura Acad Romane, 2016)
The effects of eucalyptus kraft pulping conditions on subsequent bleaching were investigated. Three samples of industrial eucalyptus chips underwent haft pulping with different alkalinities and hexenuronic acid (HexA) content. Pulp was bleached by the sequence OD(EP)DP. Decreasing the cooking temperature reduced phenolic group content and the S:G ratio of residual lignin. Reducing temperature in haft pulping resulted in better oxygen delignification and had better results whenever low temperatures and lower alkalinities were used. The final pulp brightness was not influenced by cooking temperature or alkalinity. However, viscosity, brightness reversion and chlorine dioxide consumption were influenced by alkalinity. The S:G ratio was greater at higher temperatures. Higher kappa number had better bleachability in Pre-O-2, while samples with higher levels of HexA had lower delta kappa. No correlation was established between phenolic groups and pulp bleachability.
Keywords: oxygen delignification; residual lignin; hexenuronic acids